Taro Planthopper Tarophagus colocasiae (Matsumura) (Insecta: Hemiptera: Delphacidae: Delphacinae) - Alexander Tasi; Adam Dale (EDIS, 2021)
The taro planthopper, Tarophagus colocasiae (Matsumura), is a sap feeding insect in the family Delphacidae. It primary host plant is taro (Colocasia esculenta (L.) Schott) Originally native to Southeast Asia, Indonesia, and islands in the Pacific Ocean, Tarophagus colocasiae was first discovered in the continental United States at a garden center in Winter Haven, FL in 2015. The economic impacts of Tarophagus colocasiae in Florida are currently unknown, but it may affect the aesthetic value and saleability of nursery and landscape plants.